1991
DOI: 10.7164/antibiotics.44.45
|View full text |Cite
|
Sign up to set email alerts
|

L-687, 781, a new member of the papulacandin family of .BETA.-1,3-d-glucan synthesis inhibitors. I. Fermentation, isolation, and biological activity.

Abstract: A new /M,3-D-glucan synthesis inhibitor, L-687,781 is produced by the cultivation of Dictyochaeta simplex ATCC20960. L-687,781 exhibits potent in vitro antifungal activity as well as anti-Pneumocystis activity in a rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Recent studies have also demonstrated the potential clinical usefulness of ␤-glucan as potential marker for pneumocystis pneumonia (PcP) in serum and bronchoalveolar lavage fluid (BALF) (19)(20)(21)(22)(23)(24)(25). Inhibition of Pneumocystis ␤-glucan synthase may provide, in part, an alternative treatment option for patients with PcP (2,7,(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%
“…Recent studies have also demonstrated the potential clinical usefulness of ␤-glucan as potential marker for pneumocystis pneumonia (PcP) in serum and bronchoalveolar lavage fluid (BALF) (19)(20)(21)(22)(23)(24)(25). Inhibition of Pneumocystis ␤-glucan synthase may provide, in part, an alternative treatment option for patients with PcP (2,7,(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%
“…In Saccharomyces cerevisiae, GS consists of at least two subunits: a putative catalytic subunit encoded by related genes FKS1 and FKS2 (7,10) and a regulatory subunit, a GTP-bound protein encoded by RHO1 (16). Several types of GS inhibitors, such as echinocandins (5,13), papulacandins (20), and FR901469 (8), have been identified. GS inhibitors are a new class of antifungal antibiotics with clinical significance because of their strong fungicidal activity and low toxicity (1,3).…”
mentioning
confidence: 99%
“…Nikkomycins and polyoxins are competitive inhibitors of chitin synthases (7,10,11,18). Papulacandin B (2,30,43,48), aculeacin A (29,49), echinocandin B (46), and pneumocandin B 0 (6) inhibit synthesis of 1,3-␤-glucan, most likely by inhibiting activity of 1,3-␤-glucan synthase. The killer toxin of Hansenula mrakii kills sensitive strains of S. cerevisiae by inhibiting 1,3-␤-glucan synthase activity (25,50).…”
mentioning
confidence: 99%